Distribuição intra-planta de frutos atacados de goiaba por Conotrachelus psidii Marshall, 1922 (Coleoptera: Curculionidae) em cultivo orgânico - Valente, Fabricio Iglesias [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The main focus of the organic system is the economic and ecological sustainability of ecosystem. The knowledge of the behavior of a pest is critical to the understanding of the intensity of their damage. This work was conducted to evaluate the vertical distribution of fruits attacked by C. psidii, as well the preferred side of the plant for feeding and oviposition on Guava fruits, and also evaluate the survival of larvae in the thirds and sides of the guava trees. The assay was developed in an organic guava orchard with approximately 3 ha. The cultivar was Paluma and the property is certified by IBD and FLO (Fair Trade). The orchard is located in the municipality of Fernando Prestes, São Paulo State, and the the data was collected in the 2012/2013 harvest. The rows of trees in culture were arranged in north-south direction, these trees are connected to each other in the direction of the row ( north-south), the canopy were divided into two sides , the east side ( sunrise side ) and the west side ( sunset side). The evaluations were performed fortnightly. During each assessment, 30 plants were used, chosen randomly within the plot. Each plant was divided into east and west sides, in addition to this division, the plant canopy was also divided into thirds. The assessed plants were marked for its not be used again in the experiment. In each of thirds on both sides of the plants were randomly collected five fruits, totaling thirty fruits per plant. Which was registered the number of ovipositions and feeds on fruits. To observe an oviposition, it was opened to determine whether the egg or larva was alive. In the evaluation period, we sampled 6,300 fruits, of which 50.65% had signs of oviposition. The period of feeding and oviposition occurred from December to March. Finding the beginning of this period can serve as a basis to take a decision during the monitoring of the culture, since the species ...

O principal foco do sistema de cultivo orgânico é a sustentabilidade econômica e ecológica do agroecossistema. O conhecimento do comportamento de uma praga é fundamental para o entendimento da intensidade de seus danos. O presente trabalho teve como objetivo avaliar a distribuição vertical de frutos atacados por C. psidii, o lado preferencial da planta, para alimentação e oviposição nos frutos de goiaba, assim como avaliar a intensidade de frutos atacados com larvas nos terços e lados da planta. O experimento foi realizado em um pomar orgânico de goiaba de aproximadamente 3 ha. da cultivar Paluma, certificado pelo IBD e o FLO (Fair Trade), situado no município de Fernando Prestes, Estado de São Paulo, na safra agrícola de 2012/2013. As linhas das plantas na cultura estavam dispostas no sentido norte-sul, ligadas umas às outras no sentido entre planta (norte-sul), sendo a copa dividida em dois lados, lado Leste (lado do Sol nascente) e o lado Oeste, (lado do Sol poente). As avaliações foram realizadas quinzenalmente, e em cada avaliação, foram utilizadas 30 plantas, escolhidas aleatoriamente dentro do talhão. Cada planta foi dividida nos lados leste e oeste, além desta divisão, o dossel das plantas também foi subdividido em terços. As plantas avaliadas foram marcadas para que não fossem utilizadas novamente no experimento. Em cada um dos terços de ambos os lados das plantas foram coletados aleatoriamente cinco frutos, totalizando trinta frutos por planta. Nestes os frutos foram registrados o número de orifícios de alimentação e de oviposição. Ao constatar uma postura, esta era aberta com faca para determinar apresentar a presença de ovo ou de larva viva. No período de avaliações, foram amostrados 6.300 frutos, dos quais 50,65% tinham orifícios de oviposição. O período de alimentação e oviposição do inseto ocorreu de dezembro a março. A constatação ...
Keywords: Goiaba; Goiaba - Doenças e pragas; Coleoptero; Inseto; Agricultura orgânica; Insects